In vivo measurement of volumetric wear of a total knee replacement. - Gill, H; Waite, J; Short, A; Kellett, C; Price, A; Murray, D (2006)
A new Roentgen Stereophotogrammetric Analysis (RSA) system is reported; it can measure penetration of the metallic femoral component of a Total Knee Replacement (TKR) prosthesis into the polyethylene bearing on the tibial component. This system was used to analyse a study group of six Anatomic Graduated Components (AGC) knee prostheses more than 6 years post-implantation, and to compare with a control group of six newly implanted AGC prostheses. The volumetric loss of polyethylene was estimated by imaging each prosthesis at a series of different knee flexion angles. The mean difference between the RSA measured polyethylene bearing thickness and the manufacturer's quoted values for the control group was -0.03 mm (SD 0.17). The estimated linear penetration at 6.4 years in this prosthesis was determined to be 0.1 mm/year. Volumetric wear was estimated to be 600-700 mm(3)/year at 6.4 years, equating to approximately 100 mm(3)/year. This does not appear to be clinically significant amount of wear as this prosthesis has excellent survival at 10 years.